Analysis of The Influence of Literacy, Inclusion and Financial Management on The Performance And Sustainability of Msmes In Binjai City - Ernawati, Erin; Nurlaila, Nurlaila; Syahriza, Rahmi (Dinasti International Journal of Economics, Finance & Accounting, 2024)
This study analyzes the impact of literacy inclusion and financial management on the performance and sustainability of Micro, Small, and Medium Enterprises (MSMEs) in Binjai City, North Sumatra. Utilizing a quantitative research method, the study collected primary data through questionnaires and interviews with 105 MSME owners. The findings indicate that higher financial literacy and inclusion significantly enhance the ability of MSME owners to manage business finances, thereby improving both performance and sustainability. The study highlights the critical role of financial management in the growth and stability of MSMEs, particularly in distinguishing between personal and business finances. Moreover, it confirms that well-managed finances positively influence sales turnover and decision-making processes within MSMEs. The research contributes to understanding the factors that drive MSME success in a regional context, offering practical implications for policy and training programs aimed at improving financial literacy and inclusion among MSME operators.